The Importance of a Group of Reliable Markers in Determining the Relationship between Uromodulin and Oxidative Stress - Khalilova Feruza Abdujalolovna (American Journal of Biomedicine and Pharmacy, 2025)
To determine the relationship between uromodulin and the presence of oxidative stress, it is necessary to assess the level of malondialdehyde in the blood serum, which is considered a reliable marker of the latter condition. It is known that oxidative stress occurs as a result of an imbalance between the oxidation and antioxidant systems. In this case, the process proceeds with a predominance of the oxidation process, resulting in cell damage.